Dietary protein and the glycemic index handle insulin resistance within a nutritional program for avoiding weight regain after energy-restricted induced weight loss - Fernando Vidal-Ostos; Omar Ramos-Lopez; Susan A. Jebb; Angeliki Papadaki; Andreas F. H. Pfeiffer; Teodora Handjieva-Darlenska; Marie Kunešová; Ellen E. Blaak; Arne Astrup; J. Alfredo Martinez; Diet, Obesity, and Genes (Diogenes) Project (Nutrition & Metabolism, 2022)
Abstract Background and aim The role of dietary protein and glycemic index on insulin resistance (based on TyG index) within a nutritional program for weight loss and weight maintenance was examined. Methods This study analyzed 744 adults with overweight/obesity within the DIOGenes project. Patients who lost at least 8% of their initial weight (0–8 weeks) after a low-calorie diet (LCD) were randomly assigned to one of five ad libitum diets designed for weight maintenance (8–34 weeks): high/low protein (HP/LP) and high/low glycemic index (HGI/LGI), plus a control. The complete nutritional program (0–34 weeks) included both LCD plus the randomized diets intervention. The TyG index was tested as marker of body mass composition and insulin resistance. Results In comparison with the LP/HGI diet, the HP/LGI diet induced a greater BMI loss (p < 0.05). ∆TyG was positively associated with resistance to BMI loss (β = 0.343, p = 0.042) during the weight maintenance stage. In patients who followed the HP/LGI diet, TyG (after LCD) correlated with greater BMI loss in the 8–34 weeks period (r = −0.256; p < 0.05) and during the 0–34 weeks intervention (r = −0.222, p < 0.05) periods. ΔTyG1 value was associated with ΔBMI2 (β = 0.932; p = 0.045) concerning the HP/LGI diet. Conclusions A HP/LGI diet is beneficial not only for weight maintenance after a LCD, but is also related to IR amelioration as assessed by TyG index changes. Registration Clinical Trials NCT00390637.